Small-scale inland fisheries in Africa: How to collect data for poverty assessment? - Rudolf Witt; Diemuth E. Pemsl; Hermann Waibel (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Accurate poverty assessments in developing countries require efforts to collect detailed household level data. Especially in Africa, such procedures are time consuming, expensive and can be subject to numerous constraints. In this paper we discuss the procedure of the collection of data on consumption, income and assets from poor households involved in small-scale inland fisheries as well as agricultural activities. A sampling scheme has been developed that captures the heterogeneity in ecological conditions and the seasonality of livelihood options. Sampling includes a three point panel survey of 300 households. The respondents belong to four different ethnic groups randomly chosen from three strata representing different ecological zones. In the first part of the paper the methodological framework, the survey design and interview procedure adapted to the conditions in Northern Cameroon is discussed. The second part of the paper presents selected results of the baseline study on consumption, income and assets for different types of households. In addition the record of past ecological, economic and social shocks is presented.
Keywords: 330